Indigenous versus foreign innovation and ecological footprint: Dynamic threshold effect of corruption - Muhammad Salman; Donglan Zha; Guimei Wang (Environmental and Sustainability Indicators, 2022)
As humanity's quest for natural resources is progressively exceeding Earth's biological rate of regeneration, environmental issues such as greenhouse gas accumulation in the atmosphere, ocean acidification and groundwater depletion is accelerating. The ecological footprint provides a method for measuring how much lands can support the consumption of the natural resources. This study examines in depth the role of indigenous and foreign innovation on ecological footprint as well as the potential interaction between them in 105 countries classified into developed and developing countries. In addition, we consider the effect of corruption on ecological footprint using dynamic panel threshold regression over the period from 1992 to 2017. The Cross-Sectionally Augmented Autoregressive Distributed Lag (CS-ARDL) estimator is used to tackle the heterogeneity and cross-sectional dependence in the data. The results demonstrate that indigenous and foreign innovations and their interaction significantly reduce ecological footprint in developed countries. By contrast, indigenous and foreign innovations have a crowding-out effect on ecological footprint in developing countries. Based on the dynamic threshold regression results, the indigenous and foreign innovations and their interaction significantly increase ecological footprint of developed countries when corruption crosses the threshold point. In developing countries, when corruption exceeds the threshold point, the inhibiting effects of indigenous and foreign innovations and their interaction further increase. For control variables, economic growth and urbanization significantly increase ecological footprint of these countries. Finally, developed and developing countries should collaborate to build comprehensive sustainable growth mechanisms in order to make resource-friendly technologies affordable for all income level countries.